Knowledge and hindrances in implementing lean construction by small and medium contractors in Malaysia / Wan Mohd Nurdden Wan Muhammad - Wan Muhammad, Wan Mohd Nurdden (2013)
Malaysian construction industry is having problem of producing high wastage and low productivity. Lean construction is an approach which is feasible to cope with the situation and it will be more significant to be applied by the majority parties in Malaysian construction industry, small and medium enterprises. Therefore, the aim of this research is to ascertain the lean construction implementation at small and medium scale contractor companies. The first objective of the research is to study the concept of lean construction including its components and how it is applied in construction industry. It was found through literature review that lean construction components comprise of principles, criteria and tools in order to implement it and it is designated to add value and eliminate the non added value in acquiring construction end product. The second objective is to identify level of knowledge on lean construction among professionals in small and medium scale contractor companies while the third objective is to determine factors that hinder the implementation of lean construction faced by professionals in small and medium scale contractor companies. Quantitative method was used to analyse respondents' feedback. Data was analysed using average index and severity index analyses. The result showed that knowledge level on lean construction among professionals in small and medium scale contractor companies is high and issues of lack of training and knowledge improvement. poor communication between parties involve and low understanding on lean construction concept are the most severely factors that hindering professionals in small and medium scale contractor companies from implementing lean construction.